Diffusion-Weighted Magnetic Resonance Imaging to Evaluate Major Salivary Gland Function Before and After Radiotherapy - Dirix, Piet; De Keyzer, Frederik; Vandecaveye, Vincent; Stroobants, Sigrid; Hermans, Robert; Nuyts, Sandra (International journal of radiation oncology, biology, physics, 2008)
To evaluate diffusion-weighted (DW)-MRI as a noninvasive tool to investigate major salivary gland function before and after radiotherapy (RT) for head and neck cancer (HNC). DW-MRI was performed in 8 HNC patients before and after parotid-sparing RT (mean dose to the contralateral parotid gland <26 Gy). A DW sequence was performed once at rest and then repeated continuously during salivary stimulation. Apparent diffusion coefficient (ADC) maps for both parotid and submandibular glands were calculated. Findings were compared with salivary gland scintigraphy. Before RT, the mean ADC value at rest was significantly lower in the parotid than in the submandibular glands. During the first 5 min of stimulation, the ADC value of the salivary glands showed a decrease, followed by a steady increase until a peak ADC, significantly higher than the baseline value, was reached after a median of 17 min. The baseline ADC value at rest was significantly higher after RT than before RT in the nonspared salivary glands but not in the spared parotid glands. In the contralateral parotid glands, the same response was seen as before RT. This pattern was completely lost in the nonspared glands. These results corresponded with remaining or loss of salivary function, respectively, as confirmed by salivary gland scintigraphy. Diffusion-weighted-MRI allows noninvasive evaluation of functional changes in the major salivary glands after RT and is a promising tool for investigating radiation-induced xerostomia.